Fiqh al-Lughah dalam Perspektif Literatur Arab : Telaah Konseptual dan Aplikatif (International Forum of Researchers and Lecturers, 2025)
Fiqh al-Lughah is a branch of Arabic linguistics that explores the historical, semantic, and structural aspects of the Arabic language in depth. This study aims to analyze the concept of Fiqh al-Lughah from the perspective of Arabic literature and explore its application in contemporary linguistic studies. Using a literature review method, this research examines various classical and modern sources discussing the development of Fiqh al-Lughah in both theoretical and applied contexts, including translation, text analysis, and language education. The findings indicate that Fiqh al-Lughah plays a crucial role in understanding semantic shifts, linguistic variations, and the intricate relationship between language, culture, and Islamic thought. Furthermore, this concept significantly contributes to the advancement of modern Arabic linguistic studies, particularly in enhancing comprehension of literary and religious texts. Therefore, this study affirms the continued relevance of Fiqh al-Lughah in Arabic language studies and its implications across various disciplines.